Diseño de manuales de funciones y procedimientos para el personal del consultorio de médicos especializados “oncología clínica y traslacional” en Bogota D.C - Monroy, Omaira (Universidad Antonio Nariño, 2022)
The main intention of this work is to design and propose procedures and functions manuals for an Oncological Medicine Clinic located in the city of Bogotá D.C., by means of the diagnosis, design, costs and benefits that these would imply, as to give guidelines and to execute in an effective and efficient way the activities carried out by each employee that works for this clinic, involving the commitment, responsibility and sense of participation for a work that in the first place must be human, since its services are directed to people who have been diagnosed with cancer and secondly to provide the best professional services, where the communication channels are effective, the processes have the minimum or null rate of errors and are executed in the shortest possible time, since the patient is in a situation where every minute must be used to the maximum.